2017
DOI: 10.1016/j.jjcc.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inferior J waves in patients with vasospastic angina might be a risk factor for ventricular fibrillation

Abstract: The results suggest that the existence of J waves, especially in the inferior leads, might be a risk factor for VF in VSA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…The present study revealed that young VA patients were more vulnerable to VF than older patients. Fumimoto et al …”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that young VA patients were more vulnerable to VF than older patients. Fumimoto et al …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the appearance or progression of ER is sometimes observed during acute myocardial ischemia in patients with coronary artery disease. Furthermore, VSA patients with ER, especially its day-to-day variation, develop VF more frequently than those without ER, even during the asymptomatic phase (2,3). On the other hand, Inamura et al reported the VSA patients with fatal arrhythmic events showed a high incidence of ER and positive for TWA during the symptom-free period, which exhibits potentially depolarization and repolarization abnormalities (4).…”
Section: Discussionmentioning
confidence: 99%
“…4 . Some CSA cases are complicated with early repolarization or Brugada syndrome ( 16 ). These patients' prognosis are unfavorable compared to those of patients with pure CSA ( 17 - 19 ).…”
Section: Discussionmentioning
confidence: 99%